EUFEMISME DALAM BAHASA INGGRIS DAN BAHASA SANGIR (SUATU ANALISIS KONTRASTIF) - Hontong, Meykel Kenedy; Lasut, Theresia M.C; Rambing, Rosalina (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2022)
Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  Â  ABSTRACTÂ  Â  Â This research is entitled â€œEuphemism in English and Sangirese language: A Contrastive Analysisâ€. The objectives of this research are to identify and classify the words and phrases of euphemism in English and Sangirese language and to analyze and describe the differences and the similarities of euphemism between the two languages. This research uses descriptive method. There are three steps to finish this research, those are preparation, data collection, and data analysis. This research uses the theories of Wardhaugh (2006:240) and Fromkin (2003:479) to find out the euphemism in English and Sangirese Language, and Lado (1957) to find out the differences and the similarities between the two languages. The English data have been collected from sociolinguistic books, articles or journals, videos, movies, and English previous researches done by student in Faculty of Humanities. Sangirese language data have been collected by interviewing some informants who are native speakers of Sangirese language. The finding shows that the differences of the categories of euphemism in both languages are: English has no categories of euphemism uses on the sea, euphemism word related to supernatural, euphemism word related to drink and food, euphemism related to human physics, euphemism word related to bathing and euphemisms related to bed, while Sangirese language has these seven things. The similarities between two languages are: English and Sangirese has euphemism words which have the same meaning, form, and function, those are euphemism word related to death, euphemism word related to unemployment, euphemism word related to criminality, euphemism word related to sex, euphemism word related to natural body function, euphemism word related to sex organs. This research expected to help the students in identifying euphemism in their languages and give knowledge to publics of what euphemism is and how important euphemism in human society.Keywords: euphemism, English and Sangirese Languages, contrastive analysis